2020
DOI: 10.21203/rs.3.rs-49578/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Characterization Among Carbapenem-resistant Escherichia coli Strains Using Enterobacterial Repetitive Intergenic Consensus Polymerase Chain Reaction (ERIC-PCR) Fingerprinting in South Africa

Abstract: Background Carbapenems belong to beta-lactam class of antibiotics usually considered as the last line of defense because they can be effective against severe infections caused by prevalent multidrug-resistant (MDR) pathogens. However, carbapenems can be deactivated by bacteria that produce carbapenemase (beta-lactamase). This study was conducted to screen for carbapenem-resistance genes (CRGs) harbored by pathogenic strains of Escherichia coli recovered from different environmental samples. We also assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…The results of uidA gene were similar to Kingsley Ehi Ebomah and Anthony Ifeanyi Okoh [21] which were (81%) of isolated E. coli positive for this gene, also in another study (83%) of isolated E. coli from gallstones in Iraq were positive for this gene [22]. In a study conducted by [23], they found that all the isolates confirmed as E. coli by biochemical tests were also found positive for uidA gene [24].…”
Section: Discussionsupporting
confidence: 71%
“…The results of uidA gene were similar to Kingsley Ehi Ebomah and Anthony Ifeanyi Okoh [21] which were (81%) of isolated E. coli positive for this gene, also in another study (83%) of isolated E. coli from gallstones in Iraq were positive for this gene [22]. In a study conducted by [23], they found that all the isolates confirmed as E. coli by biochemical tests were also found positive for uidA gene [24].…”
Section: Discussionsupporting
confidence: 71%